1988
DOI: 10.1111/j.1464-410x.1988.tb04368.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Testicular Germ Cell Tumours: an Increasing Incidence and Prevention by Chemotherapy

Abstract: Of 120 patients with germ cell tumours of the testis, 6 (5%) developed contralateral tumours; 63 patients received cisplatin-based combination chemotherapy for metastatic disease and none developed contralateral disease. By contrast, of 57 patients treated with orchiectomy alone or abdominal radiotherapy, 5 (8.8%) developed contralateral disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 10 publications
2
15
1
Order By: Relevance
“…No case of contralateral testicular cancer was observed among 656 patients treated with chemotherapy (median follow-up 7.7 years) [2], In 3 smaller series, also no patient was iden tified who developed a second testicular cancer after cisplatin-based chemotherapy [1,10,11]. Considering only patients who had their first tumor in the testis, we observed 3 cases (0.8%) of metachronous testicular germ cell cancer after cisplatin-containing chemotherapy.…”
Section: Resultsmentioning
confidence: 90%
“…No case of contralateral testicular cancer was observed among 656 patients treated with chemotherapy (median follow-up 7.7 years) [2], In 3 smaller series, also no patient was iden tified who developed a second testicular cancer after cisplatin-based chemotherapy [1,10,11]. Considering only patients who had their first tumor in the testis, we observed 3 cases (0.8%) of metachronous testicular germ cell cancer after cisplatin-containing chemotherapy.…”
Section: Resultsmentioning
confidence: 90%
“…Publications have suggested a decreased incidence as well as a delay in the appearance of metachronous GCTT after chemotherapy (Van Basten 1997) and an increased incidence of asynchronous seminoma (Sokal 1980;Thompson 1988); however, the data are controversial. The given explanation is that the results depend on selection bias in studies based on data from large single institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several authors have documented a second carcinoma in the contralateral testis following chemotherapy associated with the initial tumor. Although the frequency of meta chronous germ cell tumors following chemotherapy seems to be reduced [ 1,15], Fossa and Aass [7] as well as Dieck mann [5] have described residual CIS after chemothera py. In case of a strong desire for keeping fertility and the diagnosis of carcinoma in situ in the contralateral testis, for patients receiving chemotherapy surveillance of the opposite testis seems acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive retrospective studies have shown the preva lence of bilateral testicular tumors to range between 2.6 and 5% [1,4,13,15]. Human testicular germ cell tumors result from the malignant transformation of primordial germ cells.…”
Section: Introductionmentioning
confidence: 99%